ANALYSIS OF THE ACTIVITIES OF UKRAINIAN ENTERPRISES PRODUCING CEMENT UNDER THE CONDITIONS OF SYSTEM CHALLENGES - MISHCHUK, Halyna; DUDZIANYI, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the activity of Ukrainian cement production enterprises in conditions of systemic challenges. The steady growth of the cement market in Ukraine in 2021 relative to 2020 has been determined. However, the full-scale war in Ukraine significantly affected the activities of cement manufacturing enterprises. The hostilities on the territory of the country have led to a decrease in the demand for cement due to the suspension of construction projects and infrastructure works, as well as due to instability and economic uncertainty. This was reflected in the decrease in business activity in the cement market in Ukraine. In 2022, the number of active cement production entities decreased by 22.2% compared to 2021. The decrease in the number of business entities in the cement industry of Ukraine led to a decrease in the number of employees, particularly, the number of employees decreased by 21.8% in 2022 compared to 2021. Such trends continued in the reduction of personnel costs of cement production enterprises by 25.1% over the last year under review. It has been proven that the most noticeable negative impact of the war on the development of the cement industry in Ukraine can be traced in the dynamics of the volumes of products sold (goods, services) of enterprises in 2022 compared to 2021: the value of this indicator decreased by UAH 7,499,298.9 thousand. or more than a third. As a result, the financial results of cement production enterprises in 2022 significantly worsened compared to 2021. In general, the level of profitability of the operational activities of cement production enterprises in 2022 significantly decreased compared to the previous three years. The most significant decrease was in profitability of operational activity resulting in a reduction of this indicator to the level of -25.6% in 2022. In general, the system challenges for the development of the cement market in Ukraine derived from war require adequate strategic decisions to support this exceptionally important activity for the post-war recovery of Ukraine. The further research of business responses for the current challenges is a perspective of the further studies in the field.